KEPEMILIKAN INSTITUSIONAL DAN MULTINATIONALITY DENGAN FIRM SIZE DAN LEVERAGE SEBAGAI VARIABEL KONTROL TERHADAP TAX AVOIDANCE - Isykarima Khaleda Zia; Dudi Pratomo; Kurnia Kurnia (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2018)
This research aims to determine the influence of institutional ownership and multinationality with firm size and leverage as control variables on tax avoidance, either simultaneously or partially. The population is all of manufacturing companies listed in Indonesia Stock Exchange (IDX) period 2011 to 2015. The sampling technique that used is purposive sampling and obtained ten manufacturing companies with five-year period thus obtained fifty sample data. Data analysis method that used is panel data regression analysis. The results show that simultaneously, institutional ownership and multinationality with firm size and leverage as control variables have no significant effect on tax avoidance. Partially, institutional ownership has a significant negative effect on tax avoidance, while multinationality, firm size, and leverage have no significant effect on tax avoidance.